Transcutaneous Vagus Nerve Stimulation: A Promising Method for Treatment of Autism Spectrum Disorders - Jin, Yu; Kong, Jian (Frontiers in Neuroscience, 2017)
Transcutaneous Vagus Nerve Stimulation (tVNS) on the auricular branch of the vagus nerve has been receiving attention due to its therapeutic potential for neuropsychiatric disorders. Although the mechanism of tVNS is not yet completely understood, studies have demonstrated the potential role of vagal afferent nerve stimulation in the regulation of mood and visceral state associated with social communication. In addition, a growing body of evidence shows that tVNS can activate the brain regions associated with Autism Spectrum Disorder (ASD), trigger neuroimmune modulation and produce treatment effects for comorbid disorders of ASD such as epilepsy and depression. We thus hypothesize that tVNS may be a promising treatment for ASD, not only for comorbid epilepsy and depression, but also for the core symptoms of ASD. The goal of this manuscript is to summarize the findings and rationales for applying tVNS to treat ASD and propose potential parameters for tVNS treatment of ASD.